Bidirectional reflectance of laboratory cometary analogues to interpret the spectrophotometric properties of the nucleus of comet 67P/Churyumov-Gerasimenko. (15th November 2017) - Jost, Bernhard; Pommerol, Antoine; Poch, Olivier; Brouet, Yann; Fornasier, Sonia; Carrasco, Nathalie; Szopa, Cyril; Thomas, Nicolas
Abstract: In this work we provide measurements of the bidirectional reflectance in the VIS-NIR spectral range for a selection of laboratory samples to deduce parameters such as their visible spectrum, phase curve, hemispheric albedo and phase reddening. The aim is to simulate the reflectance of the comet nucleus in order to aid the interpretation of data from the surface of comet 67P/Churyumov-Gerasimenko (67P) acquired by the Rosetta OSIRIS imaging system. We produced a broad variety of well characterised and reproducible samples containing water ice, carbonaceous compounds and complex organic molecules. We were able to reproduce the individual global spectrophotometric parameters (albedo, spectrum, phase reddening, phase curve) of 67P by using mixtures of activated charcoal, tholins and water ice. However, no mixture was able to fit all parameters simultaneously. The samples with highest porosities best match the phase curve of 67P. Spectral considerations from our experiments show that the particle size of the darkening agent on the cometary surface should have a lower limit of a few hundred nanometres to several micrometres and cannot be dominated by particles in the range of some tens of nanometres. Furthermore, our findings indicate that the bright ice patches observed by OSIRIS and VIRTIS should be relatively dust free at small scale. Highlights: Spectrophotometric comparison of laboratory analogue samples and comet 67P/Churyumov-Gerasimenko. Reproducible samples containing water ice, tholins and carbon powders. Hemispherical albedo, bidirectional reflectance and phase reddening.